2019
DOI: 10.1101/687798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

notum1, acting downstream of pitx2, is essential for proper eye and craniofacial development

Abstract: Axenfeld-Rieger syndrome (ARS) is a rare autosomal dominant developmental disorder characterized by ocular anterior chamber anomalies with an increased risk of glaucoma and systemic defects. Mutations in the transcription factor PITX2 were the first identified genetic cause of ARS. Despite the developmental importance of PITX2 and its role in ARS, the pathways downstream of PITX2 have yet to be fully characterized. Comparative transcriptome analyses involving pitx2-enriched cell populations isolated via fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…They found that Pitx2 is expressed at e10.5 but is then quickly lost as development continues, suggesting that WNT/β-catenin signaling is essential for the maintenance of Pitx2 expression after activation by RA signaling. Interestingly, two WNT antagonists, Dkk2 and notum , were shown to be downstream of Pitx2/pitx2 with Dkk2 demonstrated to be a direct target (Gage et al 2008; Hendee et al 2019). Currently available data are not sufficient to fully understand the transcriptional landscape governing the spatio-temporal expression pattern of pitx2/pitx2 , therefore additional studies are necessary to understand what regulates its expression.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Pitx2 is expressed at e10.5 but is then quickly lost as development continues, suggesting that WNT/β-catenin signaling is essential for the maintenance of Pitx2 expression after activation by RA signaling. Interestingly, two WNT antagonists, Dkk2 and notum , were shown to be downstream of Pitx2/pitx2 with Dkk2 demonstrated to be a direct target (Gage et al 2008; Hendee et al 2019). Currently available data are not sufficient to fully understand the transcriptional landscape governing the spatio-temporal expression pattern of pitx2/pitx2 , therefore additional studies are necessary to understand what regulates its expression.…”
Section: Introductionmentioning
confidence: 99%